Host Adaptation of Tetranychus urticae Populations in Clementine Orchards with a Festuca arundinacea Cover May Contribute to Its Natural Control - Aguilar-Fenollosa, Ernestina; Pina, Tatiana; Gómez-Martínez, María A.; Hurtado-Ruiz, Mónica A.; Jaques, Josep A. (2017)
Tetranychus urticae Koch (Acari: Tetranychidae) is a key pest of clementine mandarins, Citrus clementina Tanaka (Rutaceae), in Spain. This mite is highly polyphagous and can be easily found in clementine orchards, both in the trees and in the associated flora. In a previous study we found that the use of a cover of Festuca arundinacea Schreber (Poaceae) offered a better regulation of T. urticae populations than either bare soil or the traditional wild cover, which included a mix of weed species. We hypothesized that the selection of two host races of T. urticae, specialized in F. arundinacea and C. clementina, could partly explain the results obtained in field studies (bottom-up regulation). Reciprocal transplant experiments show that sympatric deme x host combinations had higher mean fitness values for most of the parameters evaluated than the allopatric combinations in clementine, but not in F. arundinacea. Because local adaptation implies mean deme fitness to be systematically higher for the sympatric deme x habitat combinations than for the allopatric ones, these results can be taken as indicative of occurrence of local adaptation in T. urticae. Molecular genetic analyses with microsatellite markers support this conclusion and indicate that host adaptation of T. urticae found in our system may indeed contribute to a better natural regulation of this mite.